A study of Hydrogen-Deuterium exchange on the photophysical properties of Ruthenium (II) Polypyridyl complexes - Higgins, Michelle E. (Trinity College (Dublin, Ireland). School of Chemistry, 2002)
This main aim of the present study is to investigate the effect of protium-deuterium exchange on the photophysical and excited state energetics of Ru(ll) complexes by UV-Vis absorption, both steady-state and time-resolved emission spectroscopies. The three main complexes synthesised, characterised and studied are [Ru(phen)2 dppz]2+ 4, [Ru(phen)2diMedppz]2+ 8, and [Ru(phen)2 diFdppz]2+ 9. For each of these complexes, a series of partially deuterated analogues were successfully synthesised. For example, for 4, a series of complexes of the form, [Ru(dx-phen)2dy-dppz]2+, where x = 0 and 8, and y = 0, 4, 6, and 10 were prepared. These species could be used to probe: (i) the nature of the excited state and (ii) in which part of the dppz ligand (i.e. 1,10-phenanthroline (phen) or phenazine (phz)) the excited state electron is located.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin